The Decision Making Styles of Consumer, Motivated Consumer Innovation and the Effect of Perceived Risk on Purchasing (A Research On Sporting Goods) - Berna CAN; Ercan POLAT (ümit doğan üstün, 2022)
The present study aimed to examine the purchasing styles of consumers buying sports products, driven consumer innovation and the effect of perceived risk on purchasing. This research was designed according to the quantitative research model and the relational survey model was used. The research group consists of university students in Turkey. The research group consists of university students in Turkey. Group formation was carried out by criterion sampling method, which is one of the non-random sampling methods. In this context, the sample group of the research consists of 520 university students, 242 women and 278 men, who use sports products. In the research, a four-part face-to-face and online survey collection method was used as a data collection tool. In the research, "Personal Information Form" was used to determine the demographic characteristics of the participants. In addition, "Consumers' Decision-Making Styles Scale", developed by Sproles and Kendall (1968) and adapted into Turkish by Dursun, Alnıaçık and Tümer (2013), in order to determine consumers' decision-making styles, in order to measure motivated consumer innovativeness "Motivated Consumer Innovativeness Scale" developed by Vandecasteele and Guenes (2010) and adapted into Turkish by Özoğlu and Bülbül (2013), The Perceived Risk Scale, developed by Stone and Mason (1995) and adapted into Turkish by Özoğlu and Bülbül, was used to measure the risks perceived by consumers during purchasing. The data obtained in the study were analyzed through the SPSS program. When the research findings are evaluated, it is seen that there are low positive and negative relationships between the variables of monthly spending on sports products and consumers' decision-making styles, motivated consumer innovativeness and perceived risk factors. In addition, it is seen that there is a positive, low and moderately significant relationship between consumers' decision-making styles and motivated consumer innovativeness and perceived risk, as well as between perceived risk and motivated consumer innovativeness.